DESIGN AND IMPLEMENTATION OF A HEAD-MOTION CONTROLLED ELECTRIC WHEELCHAIR FOR ASSISTIVE MOBILITY IN QUADRIPLEGIC PATIENTS - Shakeel Ahmed Laghari,; Nadeem Ahmed,; Fayaz Hassan,; Erum Saba, (Spectrum of Engineering Sciences, 2025)
Quadriplegic individuals, who have lost motor control in all four limbs, require specialized assistive technologies to achieve mobility and independence. This paper presents the design and implementation of a head-motion-controlled electric wheelchair, developed to enhance the autonomy of individuals with severe physical disabilities. The system supports two operational modes: manual and automatic, with the latter utilizing head tilt gestures to control movement. A head-mounted inertial measurement unit (IMU) detects head orientation (forward, backward, left, right), and a microcontroller translates these inputs into movement commands. The mechanical structure comprises a standard wheelchair retrofitted with DC motors and a gear reduction system, while motion control is achieved using a custom-built, relay-based H-bridge motor driver. To enhance motion detection accuracy, sensor fusion is performed using a Kalman filter. Experimental evaluation shows that the wheelchair maintains a stable forward velocity of approximately 0.5 m/s, with smooth bidirectional turning and high command recognition reliability. The paper details the system architecture, hardware and software integration, control strategy, and performance assessment. Potential future improvements include emergency stop features via GSM, variable speed control, health monitoring, alternate input methods, and obstacle detection. The results affirm that the proposed system is a viable, cost-effective assistive solution, significantly improving mobility and quality of life for quadriplegic users.